Tailoring of microstructure in hydrogenated nanocrystalline Si thin films by ICP-assisted RF magnetron sputtering - Kyung Sik Shin (2018)
© 2015 IOP Publishing Ltd. Utilizing plasma-assisted deposition by combining an RF magnetron and an inductively coupled plasma (ICP) source it is possible to fabricate highly crystallized nc-Si:H films at a relatively low substrate temperature (300 °C). Microstructural analysis reveals enhancement in crystallinity along with (2 2 0) preferential orientation throughout the depth of the film. The possible mechanism of crystallinity enhancement and preferential orientation is presented on the basis of plasma diagnostics using optical emission spectroscopy and various film analysis tools. This work also reports the effectiveness of the ICP source and elevated temperature for the control of film microstructure and crystallinity.